Precision Breast-Conserving Surgery With Microwave Ablation Guidance: A Pilot Single-Center, Prospective Cohort Study - Pan, Hong; Qian, Mengjia; Chen, Hao; Wang, Hui; Yu, Muxin; Zhang, Kai; Wang, Siqi; Deng, Jing; Xu, Yi; Ling, Lijun; Ding, Qiang; Xie, Hui; et al. (Frontiers in Oncology, 2021)
Introduction: Negative margins in breast-conserving surgery (BCS) are essential for preventing recurrence. The aim of this study was to determine the use of preoperative microwave ablation (MWA) in the guidance of BCS for early-stage breast cancer and access whether MWA could influence the rates of positive resection margins. Methods: From 2016 to 2018, 22 women with T1/T2 invasive breast cancer were enrolled for MWA prospectively in the guidance of BCS. US-guided MWA was performed under local anesthesia, followed by BCS and sentinel lymph node biopsy (SLNB) one week after ablation. Women who underwent palpation-guided BCS directly were included as control, and propensity score matching analysis was applied. Results: MWA was performed in 22 patients. Of the 21 MWA cases with effect information, the mean tumor size in US was 20.9 ± 6.2 mm (6-37 mm). Compared with control group (BCS directly), a lower rate of positive/close margins was observed in MWA guidance group (P = 0.018), and MWA caused a higher rate of accurate surgery (the largest margin ≤ 3 cm and the smallest margin ≥ 1mm, P = 0.042). Of these 21 patients treated with MWA, 18 were candidates for SLNB. And sentinel lymph nodes were successfully identified in all cases, and no recurrence was found with a mean follow-up of 23 months. Conclusion: For patients with T1/T2 breast cancer, the application of preoperative MWA could guide BCS accurately without impairing SLNB. Clinical trials with long-term results are required to validate MWA in the guidance for breast cancer excision.